Polymers and composites manufacturing - Davim, J. Paulo; Davim, J. Paulo; Kumar, Kaushik; Kumar, Kaushik (Advanced composites ;, 2020)
This volume reviews a wide range of processing methods which are currently being used for plastics and composites. Special focus lies on advancements in automation, in development of machines and new software for modeling, new materials for ease in manufacturing and strategies to increase productivity